DEEP NERVE ULTRASONIC AUTOMATIC POSITIONING AND MAPPING METHOD, AND APPARATUS, DEVICE AND MEDIUM - XIAO, Yang (2023)
A deep nerve ultrasonic automatic positioning and mapping method, comprising: covering a target region to be positioned of a subject with a multi-array-element ultrasonic array transducer; transmitting a plurality of ultrasonic waves by means of driving the multi-array-element ultrasonic array transducer; performing focusing at any preset detection position of said target region in a human body, so as to form a focus to provide ultrasonic stimulation; and acquiring corresponding stimulation response data at an action site which is associated with a nerve to be positioned. In this way, the movement of a probe can be prevented, the target region can be automatically and completely scanned simply by means of adjusting the position of the focus formed by focusing, thereby improving coupling with the human body; and then, among a plurality of pieces of acquired stimulation response data, determining to be the position of said nerve in said target region a preset detection position which corresponds to stimulation